2013
DOI: 10.1007/s10596-013-9346-2
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modeling of hydraulic fracturing in 3D

Abstract: A procedure based on the finite element method is suggested for modelling of 3D hydraulic fracturing in the subsurface. The proposed formulation partitions the stress field into the initial stress state and an additional stress state caused by pressure build-up. The additional stress is obtained as a solution of the Biot-equations for coupled fluid flow and deformations in the rock. The fluid flow in the fracture is represented on a regular finite element grid by means of "fracture" porosity, which is the volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 34 publications
0
23
0
1
Order By: Relevance
“…We want to treat the mechanics of fracture in greater detail than in a percolation model such as Quinn, Turcotte, and Rundle [15]. On the other hand, given the desire to treat multiple interacting cracks over scales of hundreds of meters, we are forced to include less detail than in customary hydraulic fracture simulations [10]. The design goals for the numerical method are as follows:…”
Section: Simulation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We want to treat the mechanics of fracture in greater detail than in a percolation model such as Quinn, Turcotte, and Rundle [15]. On the other hand, given the desire to treat multiple interacting cracks over scales of hundreds of meters, we are forced to include less detail than in customary hydraulic fracture simulations [10]. The design goals for the numerical method are as follows:…”
Section: Simulation Methodsmentioning
confidence: 99%
“…This approach to the problem was pioneered by Clifton [6][7][8][9]. In this and more recent numerical work [10,11] it is customary to assume that fluid flow in the crack is laminar, although assumptions such as uniform height H and elliptical cross section are dropped.…”
Section: A Summary Of Theory For Elliptical Fluid-driven Crackmentioning
confidence: 99%
See 2 more Smart Citations
“…These models were used for decades in practical applications to design the hydrofracturing treatments. However, a continuous increase in both the number and size of fracking installations necessitated further development of the mathematical models describing the process, which resulted in the introduction of the so-called pseudo 3D models [45], planar 3D models [4,9,65] and recent attempts to develop fully 3D models [2,11,66,70]. A comprehensive review of the topic can be found in [2].…”
Section: Introductionmentioning
confidence: 99%